2021
DOI: 10.1042/cs20211017
|View full text |Cite
|
Sign up to set email alerts
|

Salt loading decreases urinary excretion and increases intracellular accumulation of uromodulin in stroke-prone spontaneously hypertensive rats

Abstract: Uromodulin (UMOD) is the most abundant renal protein secreted into urine by the thick ascending limb (TAL) epithelial cells of the loop of Henle. Genetic studies have demonstrated an association between UMOD risk variants and hypertension. We aimed to dissect the role of dietary salt in renal UMOD excretion in normotension and chronic hypertension. Normotensive Wistar-Kyoto rats (WKY) and stroke-prone spontaneously hypertensive rats (SHRSP) (n=8/sex/strain) were maintained on 1% NaCl for three weeks. A subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
2
3
1
Order By: Relevance
“…On the other hand, protective effects on the kidneys may also have been conferred by VCO since the salt-loaded water may have also produced an effect in the kidney. This is different from the study of Mary et al [49] who reported that there were no deleterious effects on the kidneys after 3 weeks of 1% salt-loading in SHRSPs. However, since the experiment in the current study was performed for 10 weeks, with the first death occurring at 4 weeks after the start of the salt loading, the differences in the lengths of the experiments might be attributed to the possible differences in the kidney.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, protective effects on the kidneys may also have been conferred by VCO since the salt-loaded water may have also produced an effect in the kidney. This is different from the study of Mary et al [49] who reported that there were no deleterious effects on the kidneys after 3 weeks of 1% salt-loading in SHRSPs. However, since the experiment in the current study was performed for 10 weeks, with the first death occurring at 4 weeks after the start of the salt loading, the differences in the lengths of the experiments might be attributed to the possible differences in the kidney.…”
Section: Discussioncontrasting
confidence: 99%
“…As summarized above, salt loading triggered uromodulin accumulation in TAL cells from hepsin-deficient mice [ 36 ]. These results are in line with two studies in rats, in which salt loading increased uromodulin kidney mRNA and medullary protein in normotensive Sprague–Dawley rats [ 102 ] and intracellular uromodulin retention in hypertensive [stroke-prone spontaneously hypertensive rat (SHRSP)] and normotensive rats (Wistar–Kyoto) [ 103 ]. In the latter study, 24-h uUMOD excretion was studied and decreased upon salt loading in both rat strains [ 103 ].…”
Section: Uromodulin and Sodium-sensitive Hypertensionsupporting
confidence: 90%
“…Similarly, the vasopressin analog desmopressin has been shown to increase uUMOD secretion in one study [21 ▪ ] while decreasing its secretion rate in another [8]. In the more recent study [21 ▪ ], vasopressin was found to induce a short-term increase in urinary secretion that was dependent on the protein kinase A signaling pathway that also resulted in an overall decrease in kidney levels of uromodulin. Using polarized tubular epithelial cells, the authors found that this regulation only occurred with the apical (urinary) form and not the basolateral (circulating) form.…”
Section: Regulationmentioning
confidence: 92%
“…Although water loading increases secretion of uUMOD [15–17], the effect of salt intake is debated, with some studies finding increased secretion [18,19] and others finding decreased secretion [20]. Similarly, the vasopressin analog desmopressin has been shown to increase uUMOD secretion in one study [21 ▪ ] while decreasing its secretion rate in another [8]. In the more recent study [21 ▪ ], vasopressin was found to induce a short-term increase in urinary secretion that was dependent on the protein kinase A signaling pathway that also resulted in an overall decrease in kidney levels of uromodulin.…”
Section: Regulationmentioning
confidence: 99%